The Impact of the Elite (Ulema) Class on the Ottoman Economy: The Case Study of the Cash Waqfs - Bulut, Mehmet; Korkut, Cem (International Journal of Economics, Management and Accounting, 2022)
In Muslim societies, the views of religious law scholars are critical for the community’s religiosity and the Islamicity of the state, and general socio-economic and cultural life. This study explores several financial aspects of Ottoman life governed by the Hanafi code of law and institutionalized fatwas, and the effects of the scholarly class. The Ottoman financial institutions manifested as cash waqf played a key role as credit mechanisms in the Ottoman economy. This study focuses on finance-related waqf and fatwas in the Ottoman period. This research relies on primary fatwa sources and archival waqf documents (waqfiyahs). The institutions of fatwa and cash waqf, respectively, as legal and credit institutions, had a significant effect on Ottoman socio-economic society. The fatwa institution played the role of monitoring and regulatory agency while cash waqf operated as charitable institutions and interest-free ‘banks’. Despite the religious debate around cash waqf, the latter was able to fund community development projects with no interest but also influenced the market borrowing ratio and arrangement of the borrowing methods. The study's findings show that Islam strongly influenced the economic decision-making processes in Ottoman communities. Sample of fatwas and cash waqf represent some of the most important indicators of these findings. The study will further guide recent progress made in Islamic economy and finance. The flexibility of the fatwa institution and its ability to influence decisions are also critical new instruments in Islamic finance.